2020
DOI: 10.1038/s41467-020-16362-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of glycosyl dioxolenium ions and their role in glycosylation reactions

Abstract: Controlling the chemical glycosylation reaction remains the major challenge in the synthesis of oligosaccharides. Though 1,2-trans glycosidic linkages can be installed using neighboring group participation, the construction of 1,2-cis linkages is difficult and has no general solution. Long-range participation (LRP) by distal acyl groups may steer the stereoselectivity, but contradictory results have been reported on the role and strength of this stereoelectronic effect. It has been exceedingly difficult to stu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
117
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 94 publications
(128 citation statements)
references
References 57 publications
(65 reference statements)
5
117
0
Order By: Relevance
“…Esterification on 6-OH­(entries 2–7, and entries 2–14 in Table S1) resulted in higher stereoselectivity than deoxyfluorination (entry 13), even though ester groups are less electron withdrawing than fluorine. These results further supported the ester remote assistance hypothesis during glycosylation. ,, The argument whether the ester group really stabilized the intermediate by forming a covalent glycosyl dioxolenium ion during glycosylations has not been settled, although this intermediate can be detected under extreme conditions. We observed that 6-OH esterification alone does not ensure excellent selectivity during α (1–4) glycosylations. Selectivities for the glycosylation of isopropanol ranged from 1.5–3:1 (α/β) as changes in the electronic and steric properties of ester groups had little effect (entries 2–7, and entries 2–14 in Table S1).…”
Section: Resultssupporting
confidence: 67%
“…Esterification on 6-OH­(entries 2–7, and entries 2–14 in Table S1) resulted in higher stereoselectivity than deoxyfluorination (entry 13), even though ester groups are less electron withdrawing than fluorine. These results further supported the ester remote assistance hypothesis during glycosylation. ,, The argument whether the ester group really stabilized the intermediate by forming a covalent glycosyl dioxolenium ion during glycosylations has not been settled, although this intermediate can be detected under extreme conditions. We observed that 6-OH esterification alone does not ensure excellent selectivity during α (1–4) glycosylations. Selectivities for the glycosylation of isopropanol ranged from 1.5–3:1 (α/β) as changes in the electronic and steric properties of ester groups had little effect (entries 2–7, and entries 2–14 in Table S1).…”
Section: Resultssupporting
confidence: 67%
“…The Lev group was positioned at the C-3 as O-3 ester groups are reported to assist with strong α-selectivity. 23 It was found that the Fmoc was best positioned at the C-4 position, as a C-4 AcCl group tended to migrate to the primary C-6 hydroxy group upon a C-6 Fmoc cleavage. As a result, the AcCl was used to protect the primary C-6 position in mannose building block 7 .…”
Section: Resultsmentioning
confidence: 99%
“…Due to the absence of a neighboring group at C2 position, the stereoselective synthesis of 2-deoxy glycosides is challenging [ 72 74 ]. We hypothesize that the stabilization of the oxocarbenium ion intermediate in a form of a dioxolenium ion by the remote protecting group in C3 or C6 position could be the reason for such a good α-selectivity in liquid SO 2 [ 75 ].…”
Section: Resultsmentioning
confidence: 99%